Behavioural changes in the flour beetle Tribolium confusum infected with the spirurid nematode Protospirura muricola. Issue 1 (10th September 2013) - Schutgens, M.; Cook, B.; Gilbert, F.; Behnke, J.M.
Abstract: We examined changes to the behaviour of flour beetles, Tribolium confusum, infected with the rodent stomach worm, the spirurid Protospirura muricola, in the context of the 'Behavioural Manipulation Hypothesis'. Trobolium confusum infected with the third-stage infective larvae of P. muricola showed consistently altered patterns of behaviour. Relative to uninfected beetles, over a measured time period, beetles infected with P. muricola were likely to move over a shorter distance, when moving their speed of movement was slower, they were more likely to stay in the illuminated area of their environment, more likely to emerge from darkened areas into the illuminated areas, and their longevity was significantly shortened. The changes in behaviour, as reflected in effects on speed of movement, were only evident among beetles that actually harboured infective cysts and not among those carrying younger infections when the larvae within their haemocoels would have been at an earlier stage of development and not yet capable of infecting the definitive murine hosts. We discuss whether these changes would have made the beetles more susceptible to predation by rodents, and specifically by the omnivorous eastern spiny mouse, Acomys dimidiatus, the natural definitive host of this parasite in Egypt, from where the P. muricola isolate originated, and whether they support the Behavioural Manipulation Hypothesis or reflect parasite-induced pathology.